Study the micro heat sink with pin fins and different coolants: a comparative study - Ismael Hasan, Mushtaq; Mohammed Muter, Dhay (International Journal of Engineering and Technology, 2019)
This research aims to study numerically the effect of different cooling fluids (pure fluids, Nanofluids, and Microencapsulated phase change materials suspensions) on the cooling performance of micro pin fin heat sink with different types of fins (square, triangular and circular). Three types of Nanofluids (Al2O3-water, Cu-water, TiO2-water), three types of microencapsulated phase change materials suspensions (MEPCMS) are (RT44-water, paraffin wax water, n-acted-water) and three pure fluids) Water, Oil, Ethylene Glycol) were used with constant heat flux (100 Â ) applied on the base of the heat sink. The volumetric concentrations of Nanofluids and MEPCM suspensions are (1%, 3%, and 5%) and (100 to 900) is the range of Reynolds number used in this study. A finite volume method (FVM) is used to find solutions of governor equations and boundary conditions. The results showed that using of different types of Nanofluids and MEPCM suspension lead to enhance the cooling performance of micro pin fin heat sink (MPFCHS) since it leads to increase the heat transfer 79.6% compared with pure fluids. The heat transfer in (MPFHS) for MEPCMS suspensions is higher than that for Nanofluids. However, the performance of heat sink increased with increases the concentration of Nanofluids and MEPCMS.Â
Keywords: .